Peningkatan Hasil Belajar Materi Tranformasi Energi Melalui Media Interkatif Kelas IV SD - Sophia Wydia Ningrum (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This study aims to improve student learning outcomes on the topic of energy transformation in class IV-B at Elementary SchoolJajartunggal III Surabaya by using interactive learning media. The study was conducted in two action cycles based on the classroom action research (CAR) approach. This CAR was carried out to explore and delve deeper into the use of interactive learning media to enhance the learning outcomes of class IV-B students at Elementary School Jajartunggal III Surabaya in the topic of energy transformation. The increase in grades and learning outcomes from the pre-cycle to the first cycle, and from the first cycle to the second cycle, indicates that learning with interactive media on the energy transformation topic in class IV-B at Elementary School Jajartunggal III Surabaya has a significant impact. In the pre-cycle, the average score of student learning outcomes was 21%. In the first cycle, the average score increased to 71%, which met the proficiency criteria, so the research proceeded to the next cycle. In the second cycle, with the same topic, the average student score increased and reached a passing criterion of 93%. After observing the achievement of a 93% passing rate in the second cycle, it can be concluded that this research was successful, and thus the classroom action research (CAR) was completed in the second cycle.